Technology-assisted methods to assess the quality of the therapeutic alliance between health care providers and patients: a scoping review protocol. Issue 5 (3rd May 2021) - DeArmond, Megan; Vidal, Evan; Vanier, Cheryl
ABSTRACT: Objective: The goal of this review is to identify and summarize technology-assisted methods that are being used in clinical, research, or educational settings to assess non-verbal behaviors that have been identified as contributors to the quality of the therapeutic alliance between health care providers and patients. Introduction: A strong therapeutic alliance is a critical component of positive patient outcomes. A health care provider's non-verbal behaviors help build a strong therapeutic alliance, but practice with expert feedback is often required to develop desirable non-verbal behaviors. Advances in technology have been harnessed to assess and provide feedback to health care providers, but the technological tools can be difficult to find and compare. Technology-assisted feedback has the potential to help health care providers hone important clinical skills without requiring highly trained instructors, improving medical care overall. Inclusion criteria: This review will consider quantitative and qualitative studies, as well as review articles. Participants must be health care providers (or students) who routinely conduct appointments with patients. Included studies must incorporate technology-assisted methods that are being used to collect or analyze information regarding at least one behavior associated with the therapeutic alliance in a clinical, research, or educational setting. Any type of patient encounter, whether actual, actor-based, virtual reality, or simulation-based, will be included. Methods: Five bibliographic databases will be searched, with results limited to English-language articles published from 2010 to the present. The search strategy yielded 404 results in PubMed. The proposed methodology follows the JBI methodology for scoping reviews.